DETERMINATION OF A CODE NUMBER BASED ON THE CHEMICAL COMPOSI-TION OF A BIOLOGICALLY ACTIVE SUPPLEMENT (BAS) OBTAINED FROM CISTANCHE MONGOLICA, PRODUCED AT FERGHANA STATE UNIVERSITY (Scientific journal of the Fergana State University, 2026)
The development of biologically active supplements (BAS) with therapeutic properties based on plant raw materials, which serve as a source of low-molecular-weight bioregulators, as well as the creation of regulatory and technical documentation and its implementation in practice, and the classification according to the HS Code based on chemical composition, are given special attention. In this regard, scientific research aimed at identifying the composition of biologically active compounds of the wild-growing plant species Cistanche mongolica G. Beck, developing various biologically active supplements and effective medicinal products based on them, implementing them into practice, and establishing certification criteria is of significant scientific and practical importance. This article presents the phytochemical composition of the biologically active supplement named CISTANCHE MONGOLICA, developed at Fergana State University based on the Cistanche mongolica plant growing in the territory of Uzbekistan. It describes the methods used for determining and the results obtained regarding the content of micro- and macroelements, flavonoids, amino acids, vitamins, proteins, and fats. It also outlines the classification of the produced CISTANCHE MONGOLICA supplement as a product.